The Promise of Neurolaw in Global Justice: An Interview with Dr. Pragya Mishra - Alan C. Logan; Pragya Mishra (Challenges)
In an ongoing series of interviews, Challenges Advisory Board member and Nova Institute for Health Fellow Alan C. Logan meets with thought leaders, scientists, scholars, healthcare professionals, artisans, and visionaries concerned about health at the scale of individuals, communities, and the planet. Here, Dr. Pragya Mishra responds to a set of questions posed by Challenges. Dr. Mishra, a legal academician and one of the few global scholars with a PhD specifically in neurolaw, is at the forefront of research examining the intersection of law and brain sciences. As a concept and developing field, the promise of neurolaw is that it will lead to a more equitable and less punitive justice system, one based on objective science rather than prescientific assumptions of blameworthiness and willpower. Here, Dr. Mishra reflects on the promises and pitfalls of neurolaw, the growing challenges to the free will assumptions held by the courts, and her work in a field that epitomizes a transdisciplinary effort. She discusses the place of contemplative practices within neurolaw, with special emphasis on the hope of rehabilitation. Dr. Mishra describes neurolaw through a holistic lens, one that embraces future possibilities and the shaping of evidence-based policy changes. While planetary health embraces justice as a broad term, it has paid little attention to the criminal justice system. Discussions of neurolaw are important to the ethical frameworks of planetary health. Neurolaw, as Dr. Mishra explains, is at the heart of the many interconnected challenges of our time.